Joyfull : cook effortlessly, eat freely, live radiantly - Devlukia-Shetty, Radhi; Holtzman, Rachel (Simon Element, 2024)
"A clinical dietician with a holistic approach to wellbeing presents 125 plant-based recipes to balance health with taste and meal satisfaction including French Toast Casserole, One Pot Lemony Spaghetti, Creamy Red Lentil Daal and Chocolate Mud Pie"--